(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine CRP levels and BISAP scores in patients with acute pancreatitis; To assess the prognostic value of CRP compared to BISAP in predicting the severity and necrosis of acute pancreatitis. Subjects and methods: A cross-sectional study was conducted on 100 acute pancreatitis patients who were monitored and treated at Cho Ray Hospital from December 2021 to August 2022. Results: The mean CRP levels at admission and after 48 hours were 231.6 ± 134.9 and 201.1 ± 102.0 (mg/L), respectively (p < 0.001). The BISAP score was 2.11 ± 0.96 in the severe acute pancreatitis group and 1.1 ± 0.91 in the non-severe group (p < 0.001). CRP at admission (cut-off 328 mg/L) had a prognostic value for severe acute pancreatitis and necrosis with an AUC of 0.72 (p < 0.05). CRP after 48 hours (cut-off 210 mg/L) had a prognostic value for severe acute pancreatitis with an AUC of 0.689 (p = 0.012) but no prognostic value for necrotizing acute pancreatitis. BISAP showed moderate predictive value for severe acute pancreatitis and necrotizing acute pancreatitis with AUCs of 0.771 (p < 0.001) and 0.742 (p < 0.0001), respectively. Conclusions: CRP has value in predicting the severity of acute pancreatitis, making it suitable for rapid assessment of the patient’s condition and progression to make appropriate and timely treatment decisions.